2016
DOI: 10.1159/000445836
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 3 Knockout Mice Exhibit Behaviors Consistent with Psychotic Disorders

Abstract: Neuregulin 3 (NRG3) is a paralog of NRG1. Genetic studies in schizophrenia demonstrate that risk variants in NRG3 are associated with cognitive and psychotic symptom severity, and several intronic single nucleotide polymorphisms in NRG3 are associated with delusions in patients with schizophrenia. In order to gain insights into the biological function of the gene, we generated a novel Nrg3 knockout (KO) mouse model and tested for neurobehavioral phenotypes relevant to psychotic disorders. KO mice displayed nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Examples of known human genes associated with memory also identified in our study include: NTM and KLHl20 that are associated with Alzheimer's disease and DOCK8 and KANK1 that are associated with neurodevelopmental disorders including memory potential [29][30][31]. Examples of known mouse genes associated with memory include Specc1 that was identified in a mouse genetic screen for avoidance learning [32], Prdx6 that was associated with neurogenesis and Alzheimer's disease in mice [33,34] and knock-out mice for Abl2, Nrg3, Shank2, Gria1, and Fgf14 that caused neurodevelopmental defects [35][36][37][38][39]. The other set contains 135 genes not previously associated with memory of which 65 have brain expression [40] (http:// connectivity.brain-map.org/).…”
Section: Discussionmentioning
confidence: 96%
“…Examples of known human genes associated with memory also identified in our study include: NTM and KLHl20 that are associated with Alzheimer's disease and DOCK8 and KANK1 that are associated with neurodevelopmental disorders including memory potential [29][30][31]. Examples of known mouse genes associated with memory include Specc1 that was identified in a mouse genetic screen for avoidance learning [32], Prdx6 that was associated with neurogenesis and Alzheimer's disease in mice [33,34] and knock-out mice for Abl2, Nrg3, Shank2, Gria1, and Fgf14 that caused neurodevelopmental defects [35][36][37][38][39]. The other set contains 135 genes not previously associated with memory of which 65 have brain expression [40] (http:// connectivity.brain-map.org/).…”
Section: Discussionmentioning
confidence: 96%
“…Genetic studies have reported a consistent relationship between single nucleotide polymorphisms (SNPs) located within the first intron of Nrg3 and the SZ endophenotype of delusional behavior (Morar et al, 2011). The characterization of Nrg3 −/− mice further revealed behaviors that are consistent with animal models of SZ, showing increased levels of novelty-induced hyperactivity, impaired prepulse inhibition and a reduction in fear conditioning (Hayes et al, 2016). Increased levels of Nrg3 expression in mice correlate with impulsivity, with the opposite effect seen in Nrg3-deficient mice (Loos et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Neuregulin-3 (Nrg3) is a member of the neuregulin (Nrg1-4) family of growth factors, which play important roles in the developing and mature nervous system (Birchmeier & Bennett, 2016;Grieco, Holmes, & Xu, 2018;Mei & Nave, 2014;Mei & Xiong, 2008). Nrg3 is of particular interest as it has emerged as a candidate risk gene for several neuropsychiatric disorders including bipolar disorder and schizophrenia (SZ) (Avramopoulos, 2018; P. L. Chen et al, 2009;Hayes et al, 2016;Loos et al, 2014;Paterson et al, 2017). Recent studies have also indicated that Nrg3 plays important roles in cortical development (Bartolini et al, 2017) and glutamatergic neurotransmission (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…NRG1 is essential for the development of the nervous system and heart. Thus, global deletion of NRG1 results in embryonic lethality, while knockouts of NRG2-4 develop normally (Meyer and Birchmeier, 1995;Britto et al, 2004;Hayes et al, 2016). More recently, several lines of evidence point to a role of NRGs in the control of metabolism via actions on muscle, liver, adipose tissue and the hypothalamus Zhang et al, 2018).…”
Section: The Neuregulinsmentioning
confidence: 99%